PWE-309 Intravenous lidocaine infusions for abdominal surgery. (22nd June 2015) - Craven, T; Anderson, T; Balfour, A; Paterson, H; Fearon, K; Foo, I; Speake, D
Abstract : Introduction: The Western General Hospital in Edinburgh currently performs several hundred major abdominal surgeries per year. We have adopted perioperative intravenous lidocaine infusions (PILI) as a routine analgesic adjunct for its ease of use and safety profile and have experienced improved analgesic requirements and return of gut function. Lidocaine is a sodium channel blocking amide local anaesthetic but also has secondary analgesic effects and anti-inflammatory effects. For these reasons peri-operative intravenous lidocaine infusions have been investigated for their potential to improve outcomes for patients undergoing major surgery. A recent meta-analysis of 1, 754 patients found benefit from the use of PILI especially for patients undergoing abdominal surgery. 1 We report the introduction of PILI according to a local protocol. The primary objective was to compare our safety data with that expected from the meta-analysis. Our secondary objective was to compare return of bowel function data to that reported by the Early Recovery after Surgery (ERAS) database, which collected data for all patients undergoing major colonic surgery independently of our audit. Method: The trust scientific officer waived the requirement for ethical approval as this was considered a change in clinical practice. A local protocol for the administration of PILI was suggested to local clinicians based on the available evidence. Training was delivered to recovery and high dependency unit staff who would be caring for patients receiving PILI. Data were collected prospectively using a standard anonymised paper pro forma. Results: Over a period of 24 months data on 127 uses of PILI were collected prospectively, which included 73 patients undergoing colonic resection. Lidocaine infusion was stopped early on nine (7%) occasions; three (2.4%) due to tracking up the vein and three (2.4%) patients reported parasthesiae. Three (2.4%) stoppages were for reasons later deemed to be unrelated. No other adverse events or reactions were reported. Data were available for the assessment of bowel function in 53 patients and patients in the PILI cohort who underwent colonic resection experienced a more rapid return of bowel function (return of flatus, mean days (SD): 2.84 (1.2) v 3.55 (1.7), p < 0.0001; return of bowel opening: 4.17 (2.0) v 4.81 (2.3), p = 0.014). Conclusion: PILI is a safe and easily administered peri-operative adjunct which may promote return of gut function after colorectal resection. A multicentre RCT is suggested; powered to address gut function, length of stay, opiate use and perioperative dysrhythmia following colonic resection. The forthcoming Delphi Games may be an opportunity to address this since perioperative ileus is an identified objective. Disclosure of interest: None Declared. Reference: Vigneault L, et al . Can. J. Anaesth. 2011;58:22–37